Pattern and process in host-parasitoid interactions - Hawkins, Bradford A. (Cambridge University Press, 1994)
How is the staggering biodiversity of the parasitoid insects maintained? This book, first published in 1994, explores patterns in host-parasitoid interactions, including parasitoid community richness, the importance of parasitoids as mortality factors, and their impact on host densities as determined by the outcomes of parasitoid introductions for biological control. It documents general patterns using data sets generated from the global literature and evaluates potential underlying biological, ecological and evolutionary mechanisms. A theme running throughout the book is the importance of host refuges as a major constraint on host-parasitoid interactions. Much can be learnt from the analysis of broad patterns; a few simple rules can go a long way in explaining the major components of these interactions. This book will be an invaluable resource for researchers interested in community ecology, population biology, entomology and biological control